Codifying Anti-Corruption Law in Indonesia: A Legal Necessity for Harmonization - Sholahuddin Al-Fatih; Putri Shafarina Thahir; Norhasliza binti Ghapa (Universitas Negeri Semarang, 2025)
This article aims to analyse the legal gap in anti-corruption regulations in Indonesia. Using legal research methods, this article reveals the many regulations that have the potential to hamper efforts to enforce corruption, so harmonization is necessary. The results of this research are findings regarding the urgency of harmonization of anti-corruption regulations, including; The Anti-Corruption Law, the Corruption Eradication Commission Law, UNCAC (ratified by Indonesian Government), the Money Laundering Crime Law, Criminal Code, and the Asset Confiscation Draft Law, which need to be codified into one integrated anti-corruption regulation.